Peran Guru Pendidikan Agama Islam dalam Pendidikan Moderasi: Pembentukan Sikap Moderat Siswa SMP Negeri 1 Kelumbayan Barat - Ahmad Mukhlis; Wan Jamaluddin; Dedy Irawan (WISE Pendidikan Indonesia, 2026)
Religious moderation is an important concern in Islamic Religious Education because students need to develop tolerance, fairness, openness, and respect for diversity in increasingly complex social and digital environments. This study aims to analyze the role of Islamic Religious Education teachers in developing students’ moderate attitudes at SMP Negeri 1 Kelumbayan Barat, with particular attention to the strategies used and the supporting and inhibiting factors in the process. This research employed a qualitative descriptive approach. The study was conducted at SMP Negeri 1 Kelumbayan Barat, Tanggamus Regency, Lampung, involving Islamic Religious Education teachers, ninth-grade students, the principal, and relevant school personnel selected through purposive sampling. Data were collected through classroom observation, in-depth semi-structured interviews, and documentation. The data were analyzed thematically through data reduction, data display, and conclusion drawing, while validity was strengthened through source and technique triangulation. The findings indicate that teachers developed students’ moderate attitudes through contextual learning, group discussion, question-and-answer activities, storytelling, case-based learning, personal guidance, role modeling, religious activities, and school habituation programs. Supporting factors included school leadership, collaboration among teachers, parental support, religious activities, and a positive school culture. The main obstacles were peer influence, social media exposure, family background, and students’ limited ability to manage differences constructively. This study implies that Islamic Religious Education can serve as a strategic medium for strengthening tolerance, peaceful interaction, and inclusive character formation in schools.